If it's not what You are looking for type in the equation solver your own equation and let us solve it.
n+(n+2)=76
We move all terms to the left:
n+(n+2)-(76)=0
We get rid of parentheses
n+n+2-76=0
We add all the numbers together, and all the variables
2n-74=0
We move all terms containing n to the left, all other terms to the right
2n=74
n=74/2
n=37
| n+(n+2)=766 | | a•a•a•a=4a | | 8585=x^2-5x+35 | | 2m=74.2 | | 2x-10=16x-24 | | 4/3x-7=2x-2 | | 1/c=1/c1+1/c2+1/c3 | | 5(10x-26)=3-3(x+4) | | 35x-x^2=300 | | 65=(3.1415)•x | | b/86=49.1/72.6 | | r/15+2=4 | | 7(x+2)-(6x-5)=-22 | | 12.8*(x+35.5*2)=27x | | 51-3x=6 | | 12-y=8(y-3) | | 3x+5x-10=6x+8 | | 3b+12=16 | | 3x+5(x-2)=2(3x+4) | | 14x-6=2x-6 | | 3.1x^2+x-9.6x10^-2=0 | | 5(x+4)=4x+4 | | 7x=4=2x+3 | | 7x-4=2x+34 | | 7(2x–3)=5+4(x–2) | | 4+3w=-11 | | 9v+49=16v | | x+2(8)=6 | | 5r/12-8=14 | | .24x+2(.03+3)=12 | | 6+3b=7+2b | | 5y+2y=-24y |